Global Transcriptional Analysis Reveals the Complex Relationship between Tea Quality, Leaf Senescence and the Responses to Cold-Drought Combined Stress in Camellia sinensis - Zheng, Chao; Wang, Yu; Ding, Zhaotang; Zhao, Lei (Frontiers in Plant Science, 2016)
In field conditions, especially in arid and semi-arid areas, tea plants are often simultaneously exposed to various abiotic stresses such as cold and drought, which have profound effects on leaf senescence process and tea quality. However, most studies of gene expression in stress responses focus on a single inciting agent, and the confounding effect of multiple stresses on crop quality and leaf senescence remain unearthed. Here, global transcriptome profiles of tea leaves under separately cold and drought stress were compared with their combination using RNA-Seq technology. This revealed that tea plants shared a large overlap in unigenes displayed “similar” (26%) expression pattern and avoid antagonistic responses (lowest level of “prioritized” mode: 0%) to exhibit very congruent responses to co-occurring cold and drought stress; 31.5% differential expressed genes and 38% of the transcriptome changes in response to combined stresses were unpredictable from cold or drought single-case studies. We also identified 319 candidate genes for enhancing plant resistance to combined stress. We then investigated the combined effect of cold and drought on tea quality and leaf senescence. Our results showed that drought-induced leaf senescence were severely delayed by (i) modulation of a number of senescence-associated genes and cold responsive genes, (ii) enhancement of antioxidant capacity, (iii) attenuation of lipid degradation, (iv) maintenance of cell wall and photosynthetic system, (v) alteration of senescence-induced sugar effect/sensitivity, as well as (vi) regulation of secondary metabolism pathways that significantly influence the quality of tea during combined stress. Therefore, care should be taken when utilizing a set of stresses to try and maximize leaf longevity and tea quality.